RELEVANCE OF GEOMATIC ENGINEERING VOCATIONAL CURRICULUM COMPETENCIES TOWARDS THE NEEDS OF THE INDUSTRY WORLD - Ilhan Widiasaputra; Achmad Irvan Dwi Cahyono; Achmad Nur Hasyim; Achmad Zidan Dwi Ismail; Adilla Rava Naura Ayu (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2025)
This research aims to identify the competencies of Geomatics Engineering graduates needed by the land surveying industry, and to determine the level of relevance between the graduates' competencies in the curriculum and the needs of the land surveying industry. This research is descriptive quantitative in nature, using a questionnaire instrument with five items. Data analysis was conducted using descriptive percentage analysis. The results of the study show that the level of relevance of the competencies of Geomatics Engineering graduates falls into the very relevant category